Preserving misconceptions or a call for action? - A hermeneutic re-reading of the Nativity story - Mats Målqvist (Taylor & Francis Group, 2015)
Background: Behaviour is guided by perceptions and traditions. As such, understanding culture and religion is important in order to understand healthcare behaviour. Religious perceptions shape a person's understanding of the world and are maintained through texts and tradition. One such important religious text in relation to sexual and reproductive health is the Nativity story. This account of the conception and birth of Jesus is well known in the Christian cultural sphere and beyond, and it has for generations shaped perceptions of childbirth. Methods: This paper attempts a re-reading of the Nativity story using a hermeneutic approach. Results and Conclusion: This reveals a dual understanding of the Nativity, not just as an account of immaculate transcendence and a rosy Christmas tale, but as a source of identification for pregnant women and mothers and a call to action for improved maternal and child healthcare.